The association between alcohol consumption and high risk sexual behaviour in the South African adult population. - Fawole, Olufunmilayo I (My University, 2010)
Background: South Africa is one of the countries with the highest Human Immunodeficiency Virus (HIV) prevalence in the world. The main mode of transmission in South Africa is via heterosexual intercourse. Thus there is the need to identify factors associated with HIV high risk sexual behaviour to inform future intervention programmes. Objective: To determine the association between alcohol consumption and high risk sexual behaviour in South African adults in 2006. Methods: Secondary data analysis of cross sectional study involving 1544 adult males and females, between 16-65 years interviewed in the Soul City National Survey. A multi-stage, stratified and clustered probability sampling technique was used. Univariate and multivariate analysis was done using student t test, chi square test and logistic regression models. Results: The prevalence of alcohol consumption in the week prior to the survey was 24.4% (95%CI: 22.2-26.6). The prevalence of heavy episodic drinking in last one month was 17.5% (95%CI: 15.5-19.4). There was an association between broad socioeconomic conditions and sexual behaviour particularly age, sex and race (P<0.05). The mean age at sexual debut was 17.13 (SD 2.61) years in the males and 17.91 (2.45 SD) years in females (P<0.001). Of the sexually active respondents, 12.7% and 4.2% of the men and women respectively had multiple partners currently (P<0.001). Generally consistent condom use was more in men although, only 10.3% of the men and 5.6% of the women used the condoms consistently with their casual partners (P=0.28). Multivariate regression showed that alcohol use predicted having multiple partners (AOR 2.37; 95%CI 1.19-4.69 and AOR 4.15; 95%CI 1.37-11.97) for moderate and problem drinkers respectively. Also, heavy episodic drinking predicted having multiple partners by three times (AOR 3.21; 95%CI 1.69-6.39). There was a significant dose response relationship for having multiple partners (P<0.05). As regards unprotected sexual intercourse, although not significant, female drinkers were found to be protected from inconsistent condom use with a casual partner. Male drinkers on the other hand, were found to be at a higher risk of having unprotected sex with casual partners. Perceptions of susceptibility to HIV (AOR 0.31; 95%CI 0.17-0.56), and alcohol related harm (AOR 0.17; 95%CI; 0.22-0.71) influenced consistent condom use with casual partners. Also regards gender differences, women who drank alcohol (AOR 9.68; 95%CI 1.31-17.45 vs. 1.17; 0.28-4.89) or were heavy episodic drinkers (AOR 4.45; 95%CI 1.46-3.55 vs. 2.43; 1.03-5.92) had a higher probability of having multiple partners than men. Conclusion: There is a strong association between risky alcohol use and high risk sexual behaviours. HIV prevention programmes need to address reduction in alcohol intake and changes in drinking pattern. Further research to disentangle the relationship between condom use and alcohol use is needed.
MMed, Epidemiology and Biostatistics,University of the Witwatersrand, 2009
Keywords: drinking habits; risky sexual behaviour